2014
DOI: 10.1016/j.janxdis.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Therapist-assisted Internet-delivered cognitive behavior therapy for depression and anxiety: Translating evidence into clinical practice

Abstract: This dissemination study examined the effectiveness of therapist-assisted Internet-delivered Cognitive Behavior Therapy (ICBT) when offered in clinical practice. A centralized unit screened and coordinated ICBT delivered by newly trained therapists working in six geographically dispersed clinical settings. Using an open trial design, 221 patients were offered 12 modules of ICBT for symptoms of generalized anxiety (n=112), depression (n=83), or panic (n=26). At baseline, midpoint and post-treatment, patients co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 40 publications
2
61
0
Order By: Relevance
“…The effects of Internet‐delivered cognitive behaviour therapy (iCBT) seem to be durable several years after completion of the treatment, and this model of intervention delivery appears to be as effective as face‐to‐face interventions for some psychiatric and somatic conditions (Andersson, Cuijpers, Carlbring, Riper, & Hedman, ). In addition, preliminary data suggest that iCBT can be implemented in regular health care settings without comprising the effects of validated CBT protocols for depression and anxiety disorders (e.g., El Alaoui et al, ; Hadjistavropoulos et al, ). These findings point to the Internet as a promising venue for delivering psychological interventions to target IPV; yet, to date, no study has examined whether an Internet‐delivered intervention can be used as a targeted (secondary) prevention of IPV.…”
Section: The Present Studymentioning
confidence: 99%
“…The effects of Internet‐delivered cognitive behaviour therapy (iCBT) seem to be durable several years after completion of the treatment, and this model of intervention delivery appears to be as effective as face‐to‐face interventions for some psychiatric and somatic conditions (Andersson, Cuijpers, Carlbring, Riper, & Hedman, ). In addition, preliminary data suggest that iCBT can be implemented in regular health care settings without comprising the effects of validated CBT protocols for depression and anxiety disorders (e.g., El Alaoui et al, ; Hadjistavropoulos et al, ). These findings point to the Internet as a promising venue for delivering psychological interventions to target IPV; yet, to date, no study has examined whether an Internet‐delivered intervention can be used as a targeted (secondary) prevention of IPV.…”
Section: The Present Studymentioning
confidence: 99%
“…As a multi-domain scale encompassing areas such as work, leisure activities and home life, the improvements observed in the WSAS illustrate the positive consequences of a low-intensity iCBT interventions outside of decreasing depression symptoms. Other studies utilising iCBT have recorded similar improvement in their samples [34,35,36], yet qualitative investigations may be necessary to further understand the impact of iCBT on improvements in functioning. Although preliminary in nature, these results provide support for the helpfulness of iCBT, where an effective intervention should demonstrate its ability to produce outcomes not just on disorder symptomatology, but also in the areas affected by the disorder.…”
Section: Discussionmentioning
confidence: 98%
“…A challenge facing iCBT and similar technology‐based psychotherapy applications is executing feasible dissemination from the experimental setting to the clinic without compromising treatment efficacy. There have been a handful of uncontrolled studies showing that iCBT for depression can produce medium‐to‐large within‐subject effects in a general medical setting (Hadjistavropoulos et al., ; Hedman et al., ; Hoifodt et al., ; Newby et al., ; Ruwaard, Lange, Schrieken, Dolan, & Emmelkamp, ). In addition, one effectiveness study found a large, between‐group effect when comparing iCBT and treatment as usual (Kivi et al., ).…”
Section: Discussionmentioning
confidence: 99%